What Is Text-Based Learning And Its Types In Educational Places - Gulomjonova Gulirukhsor (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Text-based Learning (TBL) has been extensively employed in EFL classrooms in Uzbekistan. The curriculum requires teachers to exploit the structure of various texts for communicative purposes. Similarly, in tertiary level, lecturers do the same thing for teaching reading, speaking, writing, and even listening. It is true that some literature offer the merits of using text-based learning. However, we also need to listen to EFL teachers’ real practice, so when implementing it in our own classroom, we, teachers, can anticipate the problem and implement the text-based learning well. This paper is aimed at presenting EFL pre-service teachers’ problems and strategies in their first-time teaching English using Text-based learning viewed from the sociocultural approach. By so doing, the problems and strategies are not only individually developed but also socially developed through social interaction or what so-called the sociocultural approach. This study is useful for secondary school teachers, lecturers, student-teachers, and policymakers in planning and implementing text-based learning.